Transformasi Pembelajaran Matematika Berbasis Numerasi Kontekstual Lokal di sekolah Menengah Alor, Nusa Tenggara Timur - Likur, Fadhillah Abdul Halik; Rosid, Tamam (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study explores the transformation of mathematics learning through the integration of local contextual numeracy in secondary schools in Alor, East Nusa Tenggara. This qualitative research using a case study approach involved learning observations, in-depth interviews with educators and students, and analysis of curriculum documents. The findings revealed that contextualizing mathematics learning by utilizing local wisdom, traditional trade practices, and local geographic phenomena was able to increase students' cognitive engagement and the relevance of the learning material. This transformation indicates a paradigm shift from procedural learning to meaningful conceptual understanding, with an emphasis on applicable numeracy literacy skills. The implementation of local context-based learning faces challenges related to limited pedagogical resources and resistance to curricular innovation. However, the integration of Alor cultural elements into mathematics learning opens up opportunities to develop culturally and contextually responsive learning models. This study contributes to the discourse on developing inclusive mathematics learning that is relevant to the socio-cultural realities of students in Indonesia's periphery